Mengungkap Penyebab Kepailitan PT. Sri Rejeki Isman Tbk (Sritex) : Faktor Internal, Eksternal, Manajemen Keuangan dan Proses Hukum - Adelia Pramadanty Darmansyah; Mulya Sahrina Auliyanti; Wafiq Zulviana Nur Azizah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
PT Sri Rejeki Isman Tbk (Sritex), a prominent player in Indonesia’s textile industry, has faced significant challenges culminating in bankruptcy. This research aims to thoroughly examine the external and internal factors that triggered the bankruptcy of Sritex and explore the legal process the company underwent. By employing a qualitative approach and descriptive analysis of secondary data, this study delves into the chronology of bankruptcy, financial management, and its economic impacts. The findings reveal that external factors, such as the impact of the COVID-19 pandemic, declining global demand, and market instability, exacerbated the company’s financial conditions. Meanwhile, internal factors, including poor debt management, a liquidity crisis, and inefficiencies in crisis management, were the primary causes of bankruptcy. The legal process in the Commercial Court commenced with the filing of a Suspension of Debt Payment Obligations (PKPU), followed by debt verification hearings, and concluded with a bankruptcy ruling that sent shockwaves through the industry. This research highlights the critical importance of robust risk management and adaptive corporate strategies to navigate global market uncertainties. Furthermore, the findings underscore the necessity of corporate governance reforms to prevent similar cases in the future.